Cardiovascular Risk and Quality of Life in Autosomal Dominant Polycystic Kidney Disease Patients on Therapy With Tolvaptan: A Pilot Study - Lai, Silvia; Mangiulli, Marco; Perrotta, Adolfo M.; Gigante, Antonietta; Napoleoni, Ludovica; Cipolloni, Elena; Mitterhofer, Anna P.; Gasperini, Maria L.; Muscaritoli, Maurizio; Cianci, Rosario; Giovannetti, Antonello; Falco, Fabiana; et al. (Current Vascular Pharmacology, 2021)
Introduction: Cardiovascular (CV) complications are the most frequent cause of morbidity and mortality in autosomal dominant polycystic kidney disease (ADPKD) patients. In 2017, the Italian Medicines Agency authorised tolvaptan, a vasopressin V2 receptor antagonist, for the treatment of ADPKD, based on the Tolvaptan Phase 3 Efficacy and Safety Study in ADPKD (TEMPO 3: 4), TEMPO 4: 4 and Replicating Evidence of Preserved Renal Function: An Investigation of Tolvaptan Safety and Efficacy (REPRISE) studies. Aim of the Study: The aim of the study was to assess the impact of tolvaptan on CV risk and quality of life, evaluated by nutritional, inflammatory, metabolic, instrumental parameters and psychocognitive tests on ADPKD patients. Methods and Materials: We evaluated 36 patients with ADPKD; 10 patients (7 males, mean age 42.5±7.0 years) treated with tolvaptan and 26 controls (11 males, mean age 36.7±9.1 years). They underwent, at T0, monthly, and at T1 (1 year) clinical, laboratory and instrumental evaluation, in addition to psychocognitive tests. Results: In ADPKD patients treated with tolvaptan, we found at T1, a decrease in carotid intima– media thickness (p=0.048), epicardial adipose tissue thickness (p=0.002), C-reactive protein (p=0.026), sympathovagal balance during night (p=0.045) and increased flow-mediated dilation (p=0.023) with a reduction in depression (Hamilton and Beck tests, p=0.008 and p=0.002, respectively) compared with controls. Conclusion: These preliminary results suggest that treatment with tolvaptan could improve early atherosclerosis and endothelial dysfunction markers and improve mood in ADPKD patients (probably by acting on endothelial cell and adipocyte V2 receptors).
Keywords: quality of life